GOVERNMENT GOODS/SERVICES PROCUREMENT IN THE UNIT KERJA PENGADAAN BARANG/JASA (UKPBJ) OF THE SEKRETARIAT DAERAH PROVINSI KALIMANTAN SELATAN - Adhanoor Yani (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2026)
This study aims to analyze the sustainable procurement process of goods/services at the planning stage, preparation for supplier selection, and implementation of supplier selection at the Goods/Services Procurement Work Unit (UKPBJ) of the South Kalimantan Provincial Secretariat, as well as to identify obstacles and strategies for overcoming them. The research uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observation, and documentation. Informants consisted of 21 procurement actors and 9 key informants, including PA/KPA, PPK, Selection Working Group, providers, and practitioners. Data analysis was carried out through data reduction, data presentation, and triangulation of sources and methods. The results of the study show that at the planning stage, there are still obstacles in the form of needs identification that is not fully supported by valid data, inaccurate timing of utilization, and budget changes. At the selection preparation stage, weaknesses were found in the preparation of technical specifications, HPS that was not supported by up-to-date data, and the practice of copying and pasting contract designs. During the selection implementation stage, obstacles included the validity of supplier qualification documents, intervention by certain parties, differences in perception among working groups, and limitations in human resources and systems. Resolution strategies were implemented through strengthening document reviews, improving human resource competencies, improving coordination, optimizing SIRUP and SPSE, and applying the principles of transparency, accountability, and sustainability. in accordance with Presidential Regulation No. 46 of 2025.